Cross-Cultural Adaptation and Validation of the Hong Kong Version of the Knee Injury and Osteoarthritis Outcome Score (HK-KOOS) for Patients with Knee Osteoarthritis - Andy S. K. Cheng; Ka-chun Chan; Sum-yuet Chan; Miu-kwan Fan; Man-kwan Fung; Oi-yan Lee; Cindy T. T. Kwok; Jackson K. K. Wong (Occupational Therapy International)
Introduction. This study aimed to validate the Hong Kong version of the Knee Injury and Osteoarthritis Outcome Score (HK-KOOS) for patients with knee osteoarthritis. Methods. Content validity was assessed using the Item and Scale Content Validity Index (I-CVI and S-CVI). Test-retest reliability and internal consistency were assessed by the Intraclass Correlation Coefficient (ICC) and Cronbach’s alpha. Dimensionality was assessed by performing exploratory factor analysis (EFA). Convergent and Divergent Validity was performed by examining the correlation between the HK-KOOS and the Chinese version of the Short Form 12 (SF-12) Health Survey, the Chinese Modified Barthel Index (C-MBI), and the Visual Analogue Scale for Pain (VAS-Pain). Ceiling and floor effects were also examined. Results. A total of 125 participants were recruited in this study. In general, all instructions, items, and response options were considered as understandable, indicating a satisfactory cross-cultural adaptation. The I-CVI and S-CVI scores were 0.80-1 and 0.90-1, respectively, indicating excellent content validity in terms of relevance, representativeness, and understandability. The test-retest reliability of all HK-KOOS subscales was satisfactory with ICC exceeding 0.70 for all domains. Cronbach’s alpha exceeded 0.80 for all subscales, indicating satisfactory internal consistency. Medium to strong correlations were found between the HK-KOOS and the VAS-Pain, SF-12, and C-MBI. However, factor analysis indicated a seven-factor structure, rather than the original five-factor structure. Items on pain and activities of daily living were loaded in the same factors. A floor effect was present in the sports and recreation subscale. Discussion and Conclusions. Future studies should further examine the dimensionality of the KOOS. The HK-KOOS is a culturally adapted, reliable, and valid outcome measure instrument to be used in Hong Kong patients with primary knee osteoarthritis.